Impact of Climate Change on Cereal Yield and Production in the Sahel: Case of Burkina Faso - IGUE, CHARLEMAGNE BABATOUNDÉ (My University, 2019)
Climate change is one of the biggest challenges of the 21st century. It affects all countries in the world, especially Sahelian countries in Africa. This paper aimed at evaluating the impact of climate change on cereal yield in Burkina Faso. The ordinary least squares (OLS) was applied to timeseries data from 1991 to 2016 collected on the World Bank website. The results have shown that temperature adversely affects yield and cereal production, while precipitation has positive effect. An increase in rainfall of 1 millimetre would increase cereal production by 385 tons in the long term and 252 tons in the short term. In the same, an increase in rainfall of 1 millimetre would increase agricultural yield by 9 kg per hectare in the long term. However, in the short term, an increase in temperatures of 1ºC would result in a decrease in cereal production and agricultural yield of 134748 tons and 72 kg per hectare, respectively. However, in the long term, a rise in temperatures of 1ºC would result in a decrease in cereal production and cereal yield of 154 634 tons and 1074 kg per hectare, respectively. Besides, the results indicate that the emission of carbon dioxide (CO2) has no significant effect on yield and cereal production. Implementing effective adaptation strategies, such as access to improved seed, introduce smart agriculture in the system of cereal in Burkina Faso and increasing irrigation infrastructure could reduce the cereal production's vulnerability to climate shocks.
Keywords: Climate change; cereal production; cereal yield; Burkina Faso